Older patients referred for geriatric consultation in the emergency department: characteristics and healthcare utilization - Mariangela Gagliano; Christophe J. Bula; Laurence Seematter-Bagnoud; Carole Michalski-Monnerat; Sylvain Nguyen; Pierre-Nicolas Carron; Cédric Mabire (BMC Geriatrics, 2023)
Abstract Background Comprehensive geriatric assessment (CGA) is difficult to perform in the emergency department (ED) environment and performance of screening tools in identifying vulnerable older ED patients who are best candidates for a geriatric consultation remain questionable. Aim To determine the characteristics of older patients referred for a geriatric consultation by ED staff and to investigate these patients’ subsequent healthcare utilization. Methods Secondary analysis of data previously collected for a prospective observational study of patients aged 75 + years visiting the ED of an academic hospital in Switzerland over four months (Michalski-Monnerat et al., J Am Geriatr Soc 68(12):2914–20, 2020). Socio-demographic, health, functional (basic activities of daily living; BADL), cognitive, and affective status data were collected at admission by a research nurse using a standardized brief geriatric assessment. Information on geriatric consultations, hospitalization, discharge destination, and 30-day readmission were retrieved from hospital database. Bivariable and multivariable analyses were performed using this data set collected previously. Results Thirty-two (15.8%) of the 202 enrolled patients were referred for a geriatric consultation. Compared to the others, they were older (84.9 ± 5.4 vs 82.9 ± 5.4 years, p = .03), more impaired in BADL (4.8 ± 1.6 vs 5.5 ± 1.0, p = .01), with more comorbid conditions (5.3 ± 1.5 vs 4.5 ± 1.9, p = .03), more frequently admitted after a fall (43.7% vs 19.4%, p = .01), and hospitalized over the previous 6-month period (53.1% vs 30.6%, p = .02). Multivariable analyses that adjusted for variables significantly associated with outcomes in bivariable analysis found that being admitted after a fall (AdjOR 4.0, 95%CI 1.7–9.4, p < .01) and previously hospitalized (AdjOR 2.7, 95% CI 1.2–6.2, p = .02) remained associated with increased odds of consultation, whereas the inverse association with BADL performance remained (AdjOR 0.7, 95%CI 0.5–0.9, p = .01). Patients referred for geriatric consultation had higher odds of hospitalization (84.4% vs 49.4%; AdjOR 5.9, 95%CI 2.1–16.8, p < .01), but similar odds of home discharge when admitted, and of 30-day readmission. Conclusion About one in six older ED patients were referred for a geriatric consultation who appeared to be those most vulnerable, as suggested by their increased hospitalization rate. Alternative strategies are needed to enhance access to geriatric consultation in the ED.